Identification of five pyrrolidinyl substituted cathinones and the collision‐induced dissociation of electrospray‐generated pyrrolidinyl substituted cathinones. Issue 5 (29th July 2016) - Qian, Zhenhua; Jia, Wei; Li, Tao; Hua, Zhendong; Liu, Cuimei
Abstract : This article reports on the analytical properties of five pyrrolidinyl substituted cathinones: α ‐pyrrolidinononaphenone ( α ‐PNP, 1 ), 4‐chloro‐ α ‐pyrrolidinopropiophenone (4‐Cl‐ α ‐PPP, 2 ), 4‐chloro‐ α ‐pyrrolidinovalerophenone (4‐Cl‐ α ‐PVP, 3 ), 5‐dihydrobenzofuranpyrovalerone (5‐DBFPV, 4 ), and 2‐(pyrrolidin‐1‐yl)‐1‐(5, 6, 7, 8‐tetrahydronaphthalen‐2‐yl)hexan‐1‐one ( β ‐THNPH, 5 ). These identifications were based on liquid chromatography–quadrupole time‐of‐flight‐mass spectrometry (LC–QTOF–MS), gas chromatography–mass spectrometry (GC–MS) and nuclear magnetic resonance spectroscopy (NMR). To our knowledge, no analytical data about α ‐PNP, 4‐Cl‐ α ‐PPP, 4‐Cl‐ α ‐PVP, and β ‐THNPH have appeared until now, making this the first report on these compounds. Moreover, in order to study the collision‐induced dissociation (CID) characteristic fragmentation routes of pyrrolidinyl substituted cathinones, a total number of 13 pyrrolidinyl substituted cathinones were selected and discussed. The major fragmentation pathways under CID mode are produced, leading to the formation of characteristic ions. Product ions of [M‐C4 H9 N] + and Cn H2n N + indicate the presence of pyrrolidinyl substitution. Characteristic fragments are also produced via the cleavages of the CH–N(CH2 )4 bond and the CO‐CHN bond. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Five pyrrolidinyl substituted cathinones α ‐PNP, 4‐Cl‐ α ‐PPP, 4‐Cl‐ α ‐PPP, 5‐DBFPV and β ‐THNPH were identified using LC‐QTOF‐MS, GC‐MS, and NMR